1999
DOI: 10.1080/08035259950170042
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and neurophysiological study of scorpion envenomation in Assiut, Upper Egypt

Abstract: Scorpion envenomation (SE) represents an agonizing problem in many countries, especially in rural areas. This clinical and neurophysiological study aimed to determine the relative frequency of scorpion envenomation in the Assiut area, in Upper Egypt. Full clinical evaluation was carried out for all children < or =18 y of age included in the study. Electroencephalography (EEG), electromyography (EMG) and motor conduction velocity measurements were carried out for a variable number of children. SE was recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
3
11
0
1
Order By: Relevance
“…In this study, similar to some other studies, hand, leg, trunk, head and neck, respectively, are more likely to be stung by scorhttp://jad.tums.ac.ir Published Online: June 30, 2020 pions (18,29,(33)(34)(35)(36). Like our results in some studies foot and hand have been more frequent bitten by scorpions (16,20,(22)(23)(24)(25).…”
Section: Resultssupporting
confidence: 86%
“…In this study, similar to some other studies, hand, leg, trunk, head and neck, respectively, are more likely to be stung by scorhttp://jad.tums.ac.ir Published Online: June 30, 2020 pions (18,29,(33)(34)(35)(36). Like our results in some studies foot and hand have been more frequent bitten by scorpions (16,20,(22)(23)(24)(25).…”
Section: Resultssupporting
confidence: 86%
“…Several authors have found similar results in terms of higher numbers of stings in boys than in girls. 14,15 Boys probably go outside more commonly and often play in places where scorpions live, such as rubbish areas in our country.…”
Section: Discussionmentioning
confidence: 99%
“…Pain and sweating with faintness constitute Stage I of envenomation [ 6 ]. Local pain and parasthesias apart, signs and symptoms of envenomation arising from exaggerated autonomic activity (parasympathetic and sympathetic) include cool extremities, vomiting, diarrhoea, hyperthermia, abdominal colic, priapism, hypotension or hypertension, sinus tachycardia, congestive heart failure, myocarditis, dysrhythmias, heart blocks and pulmonary oedema [ 31 ]. These features occur within 30 min to 4 h and can last for up to 72 h (especially tachycardia) [ 32 ].…”
Section: Venom Effects and Clinical Manifestationsmentioning
confidence: 99%
“…Sequential progress through all stages may not occur in children. The nervous system manifestations are infrequent and they include encephalopathy, seizures, restlessness, areflexia, psychosis, strokes and muscle cramps [ 31 ]. The first two neurological complications are invariably fatal in children [ 32 ].…”
Section: Venom Effects and Clinical Manifestationsmentioning
confidence: 99%